Manfaat dan Hambatan Pengembangan Pariwisata Berbasis Masyarakat di Perkampungan Budaya Betawi Setu Babakan - Devi Roza K. Kausar; Faruk Alfian; Gagih Pradini (Fakultas Pariwisata Universitas Pancasila, 2014)
This study was motivated by the existence of local groups working in arts and culture, farming, and food productions to support the Setu Babakan Betawi Cultural Village in its culture preservation and tourism purposes. The purpose of this study is to investigate the process of community empowerment through community-based tourism from the following criteria: perceived benefits and barriers in the development of community-based tourism. The theoretical bases of this study are the concept of community-based tourism and community participation in tourism development. The study reveals that community-based tourism have demonstrated benefits in the following dimensions: economic, social, cultural, environmental, and political. However, community-based tourism activities in Setu Babakan Betawi Cultural Village have not been optimum in empowering the communities due to these shortcomings: lack of tourism awareness among residents who are not directly involved with tourism, centralization of tourism-related policy and decision making within village management, and elite domination in tourism endeavours.